2017
DOI: 10.1007/s11846-017-0257-9
|View full text |Cite
|
Sign up to set email alerts
|

Modeling continuance intention towards Mobile Travel Service System (MTSS): a theoretical perspective of motivation and dependency

Abstract: This work sets up a research model that elaborates upon the development of continuance intention towards Mobile Travel Service System (MTSS) based on the motivational theory and the dependency theory. In the model, continuance intention is indirectly affected by personal innovativeness and e-interaction quality through the full mediation of e-engagement and perceived enjoyment. At the same time, the relationships between e-engagement and continuance intention and between perceived enjoyment and continuance int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 87 publications
0
5
1
Order By: Relevance
“…On the contrary to our prediction and extant studies (Chiu et al , 2017), perceived enjoyment did not contribute to attitude in LBA. A reasonable explanation is the characteristic of emotions from users' experience rather than attainment of prespecified purposes of LBA adoption (Teng, 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…On the contrary to our prediction and extant studies (Chiu et al , 2017), perceived enjoyment did not contribute to attitude in LBA. A reasonable explanation is the characteristic of emotions from users' experience rather than attainment of prespecified purposes of LBA adoption (Teng, 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…First, this study controlled social desirability in the empirical analysis to eliminate the bias caused by an individual's preference for social acceptability (Podsakoff et al , 2003). To alleviate the threat of CMV, scholars (Chiu et al , 2019; Lin et al , 2019) partialled out the effect of social desirability on outcomes (e.g. job performance) by directly controlling for social desirability (Podsakoff et al , 2003).…”
Section: Methodsmentioning
confidence: 99%
“…confirmation, trust, perceived enjoyment) and CI (e.g. Kwok et al, 2011;Tan and Kim, 2015;Chiu et al, 2019). Satisfaction is identified as the strongest predictor of CI, compared against other antecedents such as perceived usefulness (Mouakket, 2018).…”
Section: Satisfactionmentioning
confidence: 99%
“…Both satisfaction (e.g. Chang and Zhu, 2012;Chiu et al, 2019) and attitude (Amoroso and Lim, 2017; Ifinedo, 2017) have been identified as mediators between other CI antecedents (e.g. trust, perceived enjoyment) and CI.…”
Section: Attitudementioning
confidence: 99%